Do CSR actions in retailing really matter for young consumers? A study in France and Norway - Loussaïef, Leïla; Cacho-Elizondo, Silvia; Beate Pettersen, Inger; Tobiassen, Anita E. (Elsevier, 2014)
This research explores how young consumers perceive Corporate Social Responsibility (CSR) actions of French and Norwegian food retailers, and how these actions affect brand image, brand associations (adjectives, verbs, and names) and consumer–retailer relationships. It uses a qualitative methodology with in-depth interviews. This exploratory study shows that French and Norwegian young consumers have problems linking CSR with food retailing, and they question retailers' true commitment to CSR. Young French consumers had stronger brand associations than young Norwegians. Therefore, we argue that, CSR commitment among retailers in both countries is likely to positively affect retailer brand image. Nevertheless, CSR related products could also be associated with higher prices and may exclude lowincome consumers. & 2013 Elsevier Ltd. All rights reserved.
Keywords: Retailing; Brand image; Brand associations; Corporate Social Responsibility (CSR); Corporate communication; France–Norway